A study of the translation of "The Tale of Kieu" by Mạc Phi Hoàng via the use of antithesis in "Truyện Kiều" by Nguyễn Du - Định Thị Ngọc Bích (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
To study antitheses used in "The Tale of Kieu" by Mạc Phi Hoàng based on "Truyện Kiều" by Nguyễn Du; to find out the loss and gain in the use of antithesis in "The Tale of Kieu" by Mạc Phi Hoàng based on the literary work of "Truyện Kiều" by Nguyễn Du in terms of different translation methods in terms of syntax and semantics